Using patient-centered end-points in older adults participating in clinical trials - Arduino A. Mangoni; Kimberley Ruxton (Geriatric Care, 2016)
Conventional end-points, primarily based on the pharmacodynamic effects of a specific drug, are used to assess the efficacy of pharmacological treatment in clinical trials. However, their application and interpretation in complex frail older patients, a patient group with high inter-individual variability, multiple coexisting disease states and prescribed medications, is becoming increasingly questionable. National surveys and qualitative studies have convincingly shown that the maintenance of functional independence is key to self-rated health and well being in old age. Therefore, the use of unconventional, patientcentered, end-points focused on functional status and perceived health seems appropriate, in combination with conventional end-points, to comprehensively investigate the impact of pharmacological treatments in this patient group. The recent availability of objective, quantifiable, and robust scoring tools, such as the multidimensional prognostic index, to assess key functional domains and clinical outcomes offers a unique opportunity to adequately characterize patient-centered endpoints in future clinical trials in older patients.